THE EFFECT OF COST CONTROL EFFECTIVENESS AND WORKING CAPITAL TURNOVER ON FIRM VALUE IN THE FOOD AND BEVERAGE SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE - Alfian Nur Rahim (Transpublika Publisher, 2021)
This study aims to examine and analyze the Effect of Cost Control Effectiveness and Working Capital Turnover on Firm Value as an intervening variable. The sample used in this study is secondary data taken from the Indonesia Stock Exchange with 11 companies in 2011 - 2018. The hypothesis is tested using multiple linear regression. The sample used in this research is purposive sampling technique, classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test consisting of hypothesis testing, determination test and to prove the research hypothesis. The results of this study indicate that the Effectiveness of Cost Control (EPB) has a negative and significant effect on firm value. Working Capital Turnover (PMK) has a positive and significant effect on firm value. Moreover, the Effectiveness of Cost Control and Working Capital Turnover simultaneously has a positive and significant effect on Firm Value.